Genetic regulation of THBS1 methylation in diabetic retinopathy - Li, Yaqi; Gong, Chunmei; Xu, Yuanfei; Liang, Xiongshun; Chen, Xiaoping; Hong, Wenxu; Yan, Junxia (Frontiers in Endocrinology, 2022)
Background: Diabetic retinopathy (DR) is a common and serious microvascular complication of diabetes mellitus (DM), but its pathological mechanism, especially the formation mechanism of new blood vessels remains unclear. Thrombospondin-1 (THBS1) is a potent endogenous inhibitor of angiogenesis and it was found over expressed in DR in our previous study. Our study aimed to determine whether overexpression of THBS1 is associated with its promoter methylation level, and whether methylation of THBS1 is regulated by genetic variants in DR. Methods: Patients diagnosed with DR and DM patients without retinal problems were included in the case-control study. DNA methylation detection of THBS1 by bisulfite sequencing and genotyping of specific SNPs by MassARRAY analysis were performed in the patients recruited from 2019-2020. Real time quantitative PCR was performed to obtain mRNA expression of THBS1in the patients recruited from August to October 2022. The differentially methylated CpG loci of THBS1 were identified by logistic regression, and associations between 13 SNPs and methylation levels of CpG loci were tested by methylation quantitative trait loci (meQTLs) analysis. Mediation analysis was applied to determine whether CpG loci were intermediate factors between meQTLs and DR. Results: 150 patients diagnosed with DR and 150 DM patients without retinal complications were enrolled in our the first recruitmentstudy, seven DR patients and seven DM patients were enrolled in the second recruitment. The patients with DR showed promoter hypomethylation of THBS1 (P value = 0.002), and six out of thirty-nine CpG sites within two CpG islands (CGIs) showed hypomethylation(P value＜0.05). THBS1 mRNA expression in peripheral blood was significantly higher in DR patients than in DM patients. Five out of thirteen cis-meQTLs were identified to be associated with CpG sites: rs13329154, rs34973764 and rs5812091 were associated with cis-meQTLs of CpG-4 (P value=0.0145, 0.0095, 0.0158), rs11070177 and rs1847663were associated with cis-meQTLs of CpG-2 and CpG-3 respectively (P value=0.0201, 0.0275). CpG-4 methylation significantly mediated the effect of the polymorphism rs34973764 on DR (B=0.0535, Boot 95%CI: 0.004~0.1336). Conclusion: THBS1 overexpression is related to THBS1 hypomethylation in patients with DR. DNA methylation may be genetically controlled in DR.